2012
DOI: 10.1111/j.1365-3083.2012.02700.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4‐ and CD3‐T Lymphocyte Reference Values of Immunocompetent Urban and Rural Subjects in an African Nation

Abstract: Studies on the reference values of CD4 and CD3 T cells in healthy individuals have continued to gain significance because of the importance of these immunological markers in the initiation of combination antiretroviral therapy (cART). The aim of the present study was to determine and compare the reference values of CD4 and CD3 T cells in urban and rural Nigerians who were human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV) negative. After ethical clearance and informed conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(43 reference statements)
4
5
0
Order By: Relevance
“…Further, analysis of the results of this study by gender showed higher estimated mean CD4 T lymphocyte count for the female (1,238 ±398) in comparison to the male (1,046 ±399) participants. Though, difference in CD4 count was not statistically significant, it confirms previous results [5,18,21], and even among HIV-infected antiretroviral naïve subjects [24] that the females usually have higher CD4 T lymphocyte counts than the malecounterpart. However, it is pertinent to note that previous study by Zeh et al [7] among rural community dwellers in Kenya observed no significant differences by gender.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Further, analysis of the results of this study by gender showed higher estimated mean CD4 T lymphocyte count for the female (1,238 ±398) in comparison to the male (1,046 ±399) participants. Though, difference in CD4 count was not statistically significant, it confirms previous results [5,18,21], and even among HIV-infected antiretroviral naïve subjects [24] that the females usually have higher CD4 T lymphocyte counts than the malecounterpart. However, it is pertinent to note that previous study by Zeh et al [7] among rural community dwellers in Kenya observed no significant differences by gender.…”
Section: Discussionsupporting
confidence: 85%
“…(1,183 ±407 vs. 847 ±307) than the NRVs. Similarly, Adoga et al, [21] [11,12], race [5,10], diurnal rhythms [8,22], physical and psychological stress, pregnancy, drug administration [9], tuberculosis, viral infections [16], presence of anti-lymphocyte auto antibodies and procedures such as splenectomy or strenuous physical activities [13,23] have been shown to influence CD4 T lymphocyte counts in individuals. In addition, the role and characteristics of CD4 T lymphocyte cells in varied human viral infections including HIV [14] and hepatitis viruses [2, 3, 15-17, 19, 20] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the NRVs [18], and in agreement with reports from previous studies [5,21].Specifically, among different age groups we recorded higher CD4 T lymphocyte values than the NRVs in this study. This is also consistent with Adoga et al, [21], who reported higher than the NRVs.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Adoga et al, [21]reported higher (1,030 ±367 vs. 847 ±307) estimated CD4 T lymphocyte values among participants free of other viral pathogensin addition to HIV. Thus, the observed higher CD4 T lymphocyte values recorded in these studies could be as a result of screening and exclusion of participants with other pathogens capable of interference.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in sub-Saharan Africa that have investigated CD4 counts either had relatively small sample sizes [6], [7], or used convenience sampling in workers [8][13], in reproductive and general health care seekers [12], [14][18], in blood donors [14], [19], in HIV counselling and testing attendees [20]–[22], or in healthy volunteers [23], [24]. To our knowledge, the three large population-based studies reporting CD4 data did not aim to evaluate demographic and health factors that might be associated with CD4 cell counts [25][27].…”
Section: Introductionmentioning
confidence: 99%